The NYU Ultracomputer-Designing an MIMD Shared Memory Parallel Computer - Gottlieb, A; Grishman, R; McAuliffe, K P; Snir, M; Kruskal, C P; Rudolph, L (IEEE transactions on computers, 1983)
We present the design for the NYU Ultracomputer, a shared-memory MIMD parallel machine composed of thousands of autonomous processing elements. This machine uses an enhanced message switching network with the geometry of an Omega-network to approximate the ideal behavior of Schwartz's paracomputer model of computation and to implement efficiently the important fetch-and-add synchronization primitive. We outine the hardware that would be required to build a 4096 processor system using 1990's technology. We also discuss system software issues, and present analytic studies of the network performance. Finally, we include a sample of our effort to implement and simulate parallel variants of important scientific p̀rograms.